War in World Society: Towards a new order of global constitutionalism? - Hauke Brunkhorst (Global Policy, 2023)
In world society, all wars are world wars and so is the present war in Ukraine even if the use of violence is broadly restricted to the Ukrainian area (a restriction imposed clearly imposed by global politics). World society emerged between 1750 and 1850 together with the first world wars and world revolutions that were fought on all continents and oceans (1). There is no society beyond world society any longer. The world society pushes (but by no means sufficiently) (a) law and politics to institutionalise a world constitution and (b) social actors to culturally symbolise global mindsets, world views and normativity (2). Yet, only a second wave of world revolutions and world wars between 1900 and 1950 caused the rise of autonomous world law that enabled a now interrupted but still lasting global process of fully inclusive democratisation (3). However, the rise of world law in 1945 was followed by its fall after 1989, and the present wars in Ukraine and beyond come close to a complete destruction of world law. There is only a small chance to end the use of violence in Ukraine that cannot and should not lead to sufficient victory of one of the warring parties but to a reconstruction and new foundation of world law and the constitutional order of the world. The alternative is not the national state but failed states and anomia (4).
Keywords: 320